Características de la economía solidaria colombiana. Aproximaciones a las corrientes influyentes en Colombia (2018)
En Colombia, la procedencia teórica y doctrinal para la definición y conceptualización de lo que se entiende por economía solidaria no es muy clara, por esto consideramos la realización de un proyecto de investigación que nos llevará a ello. El primer resultado se presenta en este artículo. El objeto del mismo es presentar la reflexión teórica que nos permitirá tener una guía de análisis para definir la economía solidaria en Colombia. A través de una metodología cualitativa basada en el método de análisis documental y utilizando diferentes técnicas de recolección de información, analizamos dos corrientes demográficas que han tenido incidencia en la definición de la economía solidaria en Colombia. La primera es la corriente latinoamericana y la segunda es la corriente de economía social y solidaria. Finalmente hacemos una revisión del marco normativo para proponer algunos elementos teóricos que son la base de la investigación. Este artículo es la realización del primer objetivo específico del proyecto en mención. © 2018 CIRIEC-España.In Colombia, the theoretical and doctrinal origin for the definition and conceptualization of what is understood by solidary economy is not very clear, for this reason we consider the realization of a research project that will lead us to this. The first result is presented in this article. The objective is to present the theoretical reflection that will allow us to have an analysis guide to define the solidarity economy in Colombia. Through a qualitative methodology based on the method of documentary analysis and using different information collection techniques, we analyze two demographic trends that have had an impact on the definition of solidarity economy in Colombia. The first is the Latin American current and the second is the current social and solidarity economy. Finally, we review the regulatory framework to propose some theoretical elements that are the basis of the investigation. This article is the realization of the first specific objective of the project in mention. As results, we find that in Latin America we can mention two currents. The first refers to the ethical- moral current that has as main authors Luis Razeto and Pablo Guerra. The second is the economic current of the solidarity economy with important authors such as José Luis Coraggio, Max Neef and Singer. In Europe, we find a vision called social economy, its main exponents are Jose Luis Monzón and Rafael Chávez in Spain and Jean Luis Laville in France. These definitions allowed us to discuss the denomination used in Colombia and confirm that the term solidarity economy represents in Colombia an important sector that encompasses countless organizations in different parts of the national territory. These organizations are based on collective and community work seeking the solution to specific problems. Solidarity economy is another way of looking at the relationship between economy, human and his context, where he bases his actions on loyalty practices with culture, humanity, territory, in search of a balance between being, having and living. In Colombia, through Law 454 of 1998 two types of organizations are distinguished, those of solidarity economy and solidarity developed, there are organizations of a solidary nature such as cooperatives, employee funds, mutual associations but also We recognize associations, corporations, foundations, volunteer groups, community action boards, among many others that respond to the conceptual and empirical characteristics of the solidarity economy mentioned below. The main conclusions refer to the characteristics of the solidarity economy in Colombia. From the social point of view, the solidarity economy is the means to achieve the social development sought by the territories. From the economic point of view, it is a new rationality of movement, use, accumulation and relationship between the economic factor and being. From the political point of view, self-management seeks the independence of the State in relation to its decisions. However, it is a movement that projects changes within public policy focused on equity between the social, economic, cultural and environmental. From the territorial aspect, it seeks to protect the development of the territory, coexisting with its geographic and cultural context, exploring new rationalities of territory from its socio-economic and cultural practices. From the cultural point of view, it seeks to recognize its origin in solidarity, cooperative and mutualist practices, striving to rescue them again, invigorate them and encourage them from and for the territories with new forms of organization. From the environmental aspect, it seeks the generation of territorial development balanced with the environment and its social context. From the organizational point of view, it is based on the participative, valued activity towards the human being and his capacities, the self-management, the associativity, the solidarity and cooperation are transversal in the organizational structures. From the individual, considers that the person is the end and not a means, take it to their freedoms is one of the purposes so that once free contribute to the overall development of society. Finally, it seeks the participation of the human being as the end of social, political, economic and cultural relations and realities, as a leading actor that seeks continuous but dynamic and changing development, guaranteeing solidarity, cooperative and respectful coexistence with others and their environment. Unlike Latin American countries such as Brazil, Argentina and Uruguay, in Colombia the solidarity economy hardly emerges as an incipient social movement, because it does not have enough identity to give it meaning given the existing heterogeneity and diversity of practices that could be categorized as solidarity economies. The social actors that are participating in the construction of the solidarity economy are varied and diverse; unions,